230k views
0 votes
Simplify each expression using the proper order of operations. please help thank you so much :)


(41-3^2)/(√(36)*3-26 )= ?

12 +
\sqrt[3]{8} *(9-2)= ?


(28-(7^2+3))/(-13+3*5)= ?


(28)/(4) -
\sqrt[3]{8}*2^3= ?

7^2 - 5* 8+1= ?

(2*
√(16)) -(
\sqrt[3]{27}*
√(81) ) + 7= ?

User Downer
by
5.4k points

2 Answers

3 votes

Answer:


\boxed{\mathrm{view \: explanation}}

Explanation:

Apply order of operations to solve each expression.


(41-9)/(6 * 3-26)


(41-9)/(18-26)


(32)/(-8)=-4


12+2* 7


12+14=26


(28-(49+3))/(-13+15)


(28-52)/(2)


(-24)/(2) =-12


7-2 * 8


7-16=-9


49-40+1


=10


(2 * 4)-(3 * 9) +7


8-27+7


=-12

User Pleonasmik
by
4.9k points
4 votes

Answer:

a)
\boxed{-4}

b)
\boxed{26}

c)
\boxed{-12}

d)
\boxed{-9}

e)
\boxed{10}

f)
\boxed{-12}

Explanation:

1)
(41 - 3^2)/(√(36)* 3-26 )

=>
(41-9)/(6*3-26)

=>
(32)/(18-26)

=>
(32)/(-8)

=> -4

2)
12+\sqrt[3]{8} * (9-2)
\sqrt[3]{8} = 2

=>
12+2*(7)

=> 12 + 14

=> 26

3)
(28-(7^2+3))/(-13+3*5)

=>
(28-(49+3))/(-13+15)

=>
(28-52)/(2)

=>
(-24)/(2)

=> -12

4)
(28)/(4) - \sqrt[3]{8} * 2^3

=> 7 - 2 * 8

=> 7 - 16

=> -9

5)
7^2-5*8+1

=> 49 - 40 + 1

=> 9 + 1

=> 10

6)
(2 * √(16) ) - (\sqrt[3]{27} * √(81) ) + 7


√(16) = 4, \sqrt[3]{27} = 3 , √(81) = 9

=> (2 * 4) - (3 * 9) + 7

=> 8 - 27 + 7

=> -19 + 7

=> -12

User Deta Utama
by
4.5k points